The global trends and clinical progress in influenza co-infection: a visualization and bibliometric analysis (2005–2025) - Zhang, Lei; Jin, Shuang; Ma, Dabao; Liu, Zhiqiang; Ye, Jinsheng; Liu, Qingquan (Frontiers in Microbiology, 2025)
ObjectivesInfluenza co-infection, characterized by concurrent or sequential infection with influenza and other pathogens, lacks comprehensive quantitative analysis. This study evaluates the status, key hotspots, and clinical advancements in influenza co-infection research from 2005 to 2025 to guide future investigations.MethodsWe analyzed articles from 2005 to 2025 sourced from the Web of Science database using R, VOSviewer, and CiteSpace. Concurrently, we extracted clinical trials from PubMed within the same timeframe to assess advancements in the field.ResultsThe study analyzed 3,058 articles, noting a consistent rise in publications on influenza co-infection from 2005 to 2025, with a significant spike between 2020 and 2021. The United States led in publication numbers, followed by China, Germany, the United Kingdom, and France. Among these, the United Kingdom exhibited the highest international collaboration. Key collaborative centers included the Centers for Disease Control and Prevention, Emory University, and St. Jude Children's Research Hospital. “PLOS ONE” and “BMC Infectious Diseases” published the most articles, while “Journal of Virology” and “Journal of Infectious Diseases” were the most cited. Keywords such as “infection”, “virus”, “COVID-19”, “children”, and “respiratory syncytial virus” highlighted research hotspots and emerging trends in influenza co-infection. The study of pathogenic mechanisms and immune interactions in influenza-bacterial co-infection remains crucial. The COVID-19 pandemic has intensified research on the epidemiological shifts and clinical impacts of co-infection. Emphasis has also been placed on the significance of pediatric populations in influenza and respiratory viral co-infections. Clinical trials have mainly targeted preventive strategies for high-risk groups and the effects of influenza vaccination on the respiratory microbiome.ConclusionThis study comprehensively analyzes the current research landscape and identifies key hotspots in influenza co-infection. The findings offer crucial guidance for future studies in this field.